Association between predisposing factors and adults obesity from rural field practice area of a tertiary care centre, an experience from rural Bihar: a case control study - Chandra, Vikash; Choudhary, Sanjay Kumar; Kumar, Sanjay; Kumari, Abha (International Journal Of Community Medicine And Public Health, 2020)
Background: World Health Organization (WHO) defined obesity and overweight as abnormal or excessive accumulation of fat that may impair health. Obesity is a serious health issue and predisposes individuals to an increased risk of morbidity and mortality from conditions such as diabetes and hypertension. The aims and objective of this study was to identify predisposing factors associated with obesity among adults. Methods: The present case-control study was conducted among adults between 20 to 60 years of age group. The cases of obesity were identified during this study. Multi-stage sampling was done. Thus a total of 1200 subjects were studied in study setting. Pretested semi-structured proforma was used for data collection from cases and controls which involved personal interview with the respondents and clinical examination. Data was entered in Microsoft Excel 2010 after coding. Statistical analysis was done by using SPSS software. The statistical significance was evaluated at 95% confidence interval level. Results: In this study 110 obese cases and equal number of controls were compared. It is seen that the difference between cases and controls was statistically significant with regard to age (p=0.001), sex (p=0.004), occupation (p=0.000), socioeconomic status (p=0.000), education (p=0.000), tobacco use (for males only, p=0.003), physical activity (p=0.001), duration of watching TV (p=0.000) and family history of obesity (p=0.000). Conclusions: There is necessary need to health education among adults on the aspects of healthy food habits and desired lifestyles to prevent obesity/overweight and its other associated ill effects.